Ta có: (-1) + 2 + (-3) + 4 +(-5) + 6 + .....+(-9) + 10
= ( 2 + 4 +6 +....+10) + ((-1) + (-3)+(-5)+.....+(-9))
= (10 + 2).5 + ((-9) + (-1)) . 5
= ( 12+ (-10)).5
= 2.5=10
Ta có: (-1) + 2 + (-3) + 4 +(-5) + 6 + .....+(-9) + 10
= ( 2 + 4 +6 +....+10) + [(-1) + (-3)+(-5)+.....+(-9)]
= (10 + 2).5 + ((-9) + (-1)) . 5
= [(12+ (-10)].5
= 2.5
=10
(-1)+2+(-3)+4+(-5)+6+(-7)+8+(-9)+10
= [(-1)+(-9)+10]+[2+8+(-3)+(-7)]+(4+6)+(-5)
= 0+0+10+(-5)
= 10+(-5)
= 5
(-1)+2+(-3)+4+(-5)+6+(-7)+8+(-9)+10
= [(-1)+2]+[(-3)+4]+[(-5)+6]+[(-7)+8]+[(-9)+10]
= 1+1+1+1+1
= 1 . 5
= 5